Elbow Fracture in Children at Saiful Anwar General Hospital, Nine Years Experiences - Sananta, Panji; Sintong, Langga; Prasetio, Budhi; Anthony Putera, Marvin; Andarini, Sri; Kalsum, Umi; Suryanto Dradjat, Respati (Open Access Macedonian Journal of Medical Sciences, 2019)
AIM: The frequency, incidence, and types of fracture of the elbow are different between children and adult. The epidemiology of elbow fracture in children has been the subject of a limited number of studies. This study aims to observe the pattern of elbow fractures in children 18 years of age and younger, during a nine years period. METHODS: This is a retrospective study about elbow fracture cases in children 18 years old and younger treated in Saiful Anwar General Hospital Malang in the period of June 2009 until December 2018. The data obtained from the medical record include the age at the time of accidents, fracture site, type of lesion and ipsilateral injuries, time of accidents, and the mechanism of injury. RESULTS: There is a total of 99 elbow fracture, and there are 62 male (63%) and 37 female patients (37%). The mean age for the entire group is 7.3 years (8.1 years for male and 7.1 years for female). Most cases are supracondylar fracture (n=77, 78%). The supracondylar fracture is composed of 17 fracture classified to type II, and 60 fracture to type III as classified by Gartland. The most common etiology of fracture is associated with sports, recreational activities, and fall from height of less than two meters. Nerve injury involving the median, radial, and ulnar nerve is seen in eight patients with type III supracondylar fracture. Associated brachial artery injury is seen in four patients with type III supracondylar fractures. 78 patients (79%) were treated surgically and 21 patients (21%) were treated conservatively. CONCLUSION: The incidence of elbow fracture in children treated in Saiful Anwar General Hospital during a nine years period is 99 patients, with supracondylar fracture Gartland type III being the leading type of this group. Male patients are more common than female patients. Nerve injury was seen in 13.33% of cases and brachial artery injury was seen 6.67% with type III supracondylar fracture. Most of the elbow fracture in our institution were treated operatively.